Plate 4: Instruments for rocket making - Brawe, Hermann (Vollenkommene Unterweisung, wie Raketen, Feuer- Wasser- Sturm-Kugeln, Granaten, Pech-Sturm-Kräntze, und allerhand Lust und Ernsthaffte Feuer-wercke zubereiten, 1660)
Fig. 10 A: Rod to wind paper casings. B: Rod to tamp powder. C: Mallet. D: Disk used in filling rocket casings. Also depicted: Boring tool.
Keywords: Rocketry; Ordnance; Explosives; Artillery